Hibiscus rosa-sinensis L. dan Bioaktivitasnya - Marina Silalahi (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2019)
Hibiscus rosa-sinensis L. has been long used as medicine, ornamental plants, and foodstuffs. The plants uses as foodstuffs have nutritional or improve the taste, while the plants used as medicine have biocytivity compounds. This article was written based on a review of vary scientific articles and books published online and offline related to the use of H. rosa-sinensis. Hibiscus rosa-sinensis is a plant originating from China and has around 300 hybrids, which structures of corolla has vary in color and shape. In the traditional medicine of H. rosa-sinensishas been used to cure of the hypertension, diabetes mellitus, wounds, menstrual disorders, and abortion. The bioessay of H. rosa-sinensis has activity as recovery of heart disolder, hypertension, diabetes mellitus, antioxidants, antifertility, anti ulceration, and kidney disorders. Keywords: Hibiscus rosa-sinensis, hypertension, antifertility, abortion.